Dental Epithelial Stem Cells Express the Developmental Regulator Meis1 - Sanz-Navarro, Maria; Delgado, Irene; Torres, Miguel; Mustonen, Tuija; Michon, Frederic; Rice, David P. (Frontiers in Physiology, 2019)
MEIS1 is a key developmental regulator of several organs and participates in stem cell maintenance in different niches. However, despite the murine continuously growing incisor being a well described model for the study of adult stem cells, Meis1 has not been investigated in a dental context. Here, we uncover that Meis1 expression in the tooth is confined to the epithelial compartment. Its expression arises during morphogenesis and becomes restricted to the mouse incisor epithelial stem cell niche, the labial cervical loop. Meis1 is specifically expressed by Sox2+ stem cells, which give rise to all dental epithelial cell lineages. Also, we have found that Meis1 in the incisor is coexpressed with potential binding partner Pbx1 during both embryonic and adult stages. Interestingly, Meis2 is present in different areas of the forming tooth and it is not expressed by dental epithelial stem cells, suggesting different roles for these two largely homologous genes. Additionally, we have established the expression patterns of Meis1 and Meis2 during tongue, hair, salivary gland and palate formation. Finally, analysis of Meis1-null allele mice indicated that, similarly to SOX2, MEIS1 is not essential for tooth initiation, but might have a role during adult incisor renewal.